2015
DOI: 10.1016/j.annepidem.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress is associated with obesity and diet quality in Hispanic/Latino adults

Abstract: Purpose To examine the association of psychosocial stress with obesity, adiposity, and dietary intake in a diverse sample of Hispanic/Latino adults. Methods Participants were 5077 men and women, 18–74 years old, from diverse Hispanic/Latino ethnic backgrounds. Linear regression models were used to assess the association of ongoing chronic stressors and recent perceived stress with measures of adiposity (waist circumference and percentage body fat) and dietary intake (total energy, saturated fat, alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 41 publications
11
123
1
6
Order By: Relevance
“…Although several earlier studies have found association between stress and unfavorable diet quality or food choices (Barrington et al, 2014;Groesz et al, 2012;Isasi et al, 2015;Oliver & Wardle, 1999;Wardle, Steptoe, Oliver, & Lipsey, 2000), also opposite findings, in line with our results, have been reported. Perceived stress has not been associated with diet quality measured by indices such as the Alternate Healthy Eating Index (AHEI), the Dietary Approaches to Stopping Hypertension (DASH), the Mediterranean Diet Score (Ferranti et al, 2013), and the Healthy Eating Index-2010 (HEI-2010) (Richardson et al, 2015), or dietary energy density (Grossniklaus et al, 2010), intake of energy from added sugars (Barrington et al, 2014), or omega-3 polyunsaturated fatty acids intake (Suominen-Taipale et al, 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Although several earlier studies have found association between stress and unfavorable diet quality or food choices (Barrington et al, 2014;Groesz et al, 2012;Isasi et al, 2015;Oliver & Wardle, 1999;Wardle, Steptoe, Oliver, & Lipsey, 2000), also opposite findings, in line with our results, have been reported. Perceived stress has not been associated with diet quality measured by indices such as the Alternate Healthy Eating Index (AHEI), the Dietary Approaches to Stopping Hypertension (DASH), the Mediterranean Diet Score (Ferranti et al, 2013), and the Healthy Eating Index-2010 (HEI-2010) (Richardson et al, 2015), or dietary energy density (Grossniklaus et al, 2010), intake of energy from added sugars (Barrington et al, 2014), or omega-3 polyunsaturated fatty acids intake (Suominen-Taipale et al, 2010).…”
Section: Discussionsupporting
confidence: 57%
“…Different stress coping mechanisms between both sexes could also be considered as a possible cause of the different findings between men and women. For instance, perceived stress has been an important predictor of both diet quality and adiposity, and women are particularly susceptible to perceived stress (de Vriendt et al, 2012;Isasi et al, 2015;Nastaskin and Fiocco, 2015). In addition, a population-based study showed different socioeconomic determination of obesity in men and women, increasing the complexity of modeling these variables (Monteiro et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Each affirmative item was rated on a 3-point scale as “not very stressful,” “moderately stressful,” or “very stressful.” The chronic stress score was defined as the total number of stressors reported as moderately or very stressful lasting 6 months or more. 40 …”
Section: Methodsmentioning
confidence: 99%